Peptides encrypted in the human intestinal microbial-exoproteome as novel biomarkers and immunomodulatory compounds in the gastrointestinal tract. (January 2019) - Fernández-Tomé, Samuel; Montalban-Arques, Ana; Díaz-Guerra, Alba; Galvan-Roman, José M.; Marin, Alicia C.; Mora-Gutiérrez, Irene; Ortega Moreno, Lorena; Santander, Cecilio; Sánchez, Borja; Chaparro, María; Gisbert, Javier P.; Bernardo, David
Graphical abstract: The effect of 20 novel bioactive peptides encrypted on the human intestinal microbial exoproteome has been characterized on human intestinal cytokine milieu, where some of them expanded the production of tolerogenic IL-10 while inhibited secretion of pro-inflammatory IL-17A and IL-8. Moreover, serum antibody levels directed towards the peptides also displayed biomarker potential as they allowed discrimination of patients with different types of inflammatory bowel disease from healthy controls. Highlights: Identification of 20 novel bioactive peptides secreted by the gut microbiota. Serum IgA levels towards the peptides discriminate healthy controls from IBD. Peptides modulate the human intestinal cytokine milieu in the presence/absence of LPS. Bacterial peptides are revealed therefore as novel biomarkers and functional compounds. Abstract: Peptides encrypted in the intestinal microbial-exoproteome mediate the host-microbiota crosstalk, which is disrupted in inflammatory bowel disease (IBD). Here, the MAHMI database was used for the identification of 20 novel intestinal bacterial peptides. Our results revealed that serum IgA levels directed towards the peptides, but not IgG, discriminated healthy controls from IBD patients. Indeed, they also differentiated patients with ulcerative colitis from Crohńs disease and, within them, patients with and without intestinal inflammation. All peptides were immunomodulatory as they changed the intestinal cytokine milieu following human lamina propria mononuclear cells culture (with/out LPS), revealing a Bifidobacterium longum subsp. longum peptide with the highest tolerogenic properties. Therefore, bacterial peptides encrypted in the human gut metaproteome may have utility as non-invasive biomarkers to aid on IBD diagnosis and monitoring. These peptides also display immunomodulatory effects on the intestinal mucosa revealing them as novel functional compounds for non-drug therapeutic strategies in IBD.